Fishpond dams affect leaf‐litter processing and associated detritivore communities along intermittent low‐order streams. (1st August 2017) - Four, Brian; Thomas, Marielle; Arce, Evelyne; Cébron, Aurélie; Danger, Michael; Banas, Damien
Abstract: Intermittent streams are common and widespread freshwater ecosystems globally. While dams greatly affect the ecology of permanent streams, the extent of their effects on intermittent streams remains largely unknown. The physical and chemical alterations induced by dams could have particularly strong impacts on the functioning of intermittent low‐order streams, especially due to the limitations they place on colonisation of aquatic biota from downstream permanent waters. Leaf‐litter breakdown (LLB) and associated communities (microbes and shredders) were studied to investigate the potential ecological continuum rupture caused by fishpond dams along the longitudinal gradient of intermittent streams. Three to four sites were investigated along three reference (no dam) and three impacted (with a fishpond dam) first‐order intermittent low‐order streams. LLB increased along the longitudinal gradient in all six streams regardless of the presence of dams (from 1.5 to 8.4 fold over <1.5 km distance). This underscores the great variability of low‐order stream functioning even at fine scales. Such upstream to downstream gradients need to be taken into account before investigating the effect of any perturbation using LLB as a functional indicator. Fishponds dams tended to increase LLB downstream, and altered the downstream microbial communities (increase in fungal densities) and shredder assemblages (increase in Gammaridae). The effects of fishpond dams on intermittent stream functioning appeared to be most significant when they were associated with changes in hydrology, that is, when fishponds resulted in permanent flows downstream of dams. Our findings suggest that better management of fishpond dams in order to limit hydrological modifications downstream (for instance, by preventing leaks from the dam) could reduce their impact on ecosystem functioning in intermittent streams.